Prevalence, distribution and risk of sessile serrated adenomas/polyps at a center with a high adenoma detection rate and experienced pathologists - IJspeert, Joep E. G.; de Wit, Koos; van der Vlugt, Manon; Bastiaansen, Barbara A. J.; Fockens, Paul; Dekker, Evelien (Endoscopy, 2016)
Background and study aims: Sessile serrated adenomas/polyps (SSA/Ps) are the precursors of 15 % – 30 % of colorectal cancers (CRC). We aimed to determine the prevalence and distribution of SSA/Ps and to evaluate the association between SSA/Ps and the risk of synchronous advanced neoplasia at a high quality colonoscopy center.Methods: Data from all colonoscopies performed within one dedicated colonoscopy center between 2011 and 2015 were prospectively retrieved using an automated reporting system. All lesions were assessed by an experienced gastrointestinal pathologist. Multiple logistic regression was used to evaluate influence of age, gender, and colonoscopy indication on prevalence of SSA/Ps, and to assess the association between SSA/Ps and synchronous advanced neoplasia.Results: In total 4251 histologically confirmed polyps were resected in 3364 patients; 399 polyps were SSA/Ps (9.4 %). The prevalence of SSA/Ps was 8.2 % overall, increasing to 9.0 % for individuals older than 50 years. SSA/P detection rate varied between 2.5 % and 13.6 % among endoscopists. Increased SSA/P prevalence was associated with colonoscopy indications “familial CRC risk” (odds ratio [OR] 1.52, 95 % confidence interval [95 %CI] 1.05 – 2.22; P = 0.03) and “surveillance” (OR 1.73, 95 %CI 1.20 – 2.49; P < 0.01), when compared with the indication “symptoms.” The presence of synchronous advanced neoplasia was associated with SSA/Ps overall (OR 1.71, 95 %CI 1.25 – 2.34; P = 0.001), as well as with high risk SSA/Ps (defined as ≥ 10 mm and/or with dysplasia) (OR 2.70, 95 %CI 1.56 – 4.67; P < 0.001) Conclusion: SSA/Ps are more common than previously reported and are associated with the presence of synchronous advanced neoplasia. Endoscopists should be assiduous in identifying SSA/Ps in daily practice and should carefully look for synchronous advanced neoplasia when an SSA/P has been recognized. Results from this study can guide detection standards in general colonoscopy practice adapted to the type of patient that may predominate in an individual department.